0197 THE INCREASE IN HUNGER ACROSS A SLEEP AND FASTING PERIOD IS MODULATED BY THE CIRCADIAN SYSTEM. (28th April 2017) - Bowles, NP; McHill, AW; Thosar, SS; Herzig, MX; Clemons, NA; Roberts, SA; Berman, AM; Morimoto, M; Butler, MP; Emens, JS; Shea, SA
Abstract: Introduction: Appetite is affected by the size and time since a prior meal, the overnight fast, and possibly sleep itself. Additionally, there exists an endogenous circadian rhythm in appetite with a trough during the biological morning independent of calories consumed, time since prior meal, and time since waking. How these factors interact is unknown. Thus, we assessed how sleep and fasting affect appetite across the circadian cycle. Methods: Eight healthy participants (mean age, 51 years; mean BMI, 25.3 kg/m 2 ; 4 females) underwent a laboratory protocol that balanced eucaloric meals and sleep periods evenly across the circadian cycle (by scheduling 10 identical, recurrent 5h 20min 'days' in dim light thereby desynchronizing the circadian and behavioral cycles). Participants ate one identical meal each wake period and rated hunger immediately prior to sleep (30 minutes after each meal), and at the end of each sleep opportunity. Sleep was assessed with polysomnography. Salivary melatonin was used to assess circadian phase (phase marker = dim light melatonin onset [DLMO]). Results: Appetite increased across each sleep opportunity with a median increase of 32%. This increase was dependent upon circadian phase (p=0.009), with the greatest increase in hunger when participants awoke in the biological afternoon (~6hrs before DLMO; ~2:45 pm). The lowest increase in hunger across the sleep period occurred during the biological night (~2hrs after DLMO; ~10:45 pm). Group mean peak to trough difference was 8 % of the full range of the hunger scale. This circadian variation in increase in appetite across sleep was correlated with the number of arousals from sleep (p=0.038), but was not significantly associated with sleep efficiency. Conclusion: The increase in appetite across a sleep and fasting period is modulated by the circadian system, with the greatest increase when sleep occurs across the biological morning and into the afternoon. The mechanism may be related to sleep quality (number of arousals). Such results may have considerable relevance to energy balance and diet planning in people with disturbed sleep, and night shift workers who have both disturbed sleep and misalignment between meal timing and circadian phase. Support (If Any): R01 HL125893 (to SAS).